IMPROVING PATENT PROTECTION OF INVENTIVE ACTIVITY IN THE CONTEXT OF EU LEGISLATION - Philyk, Nataliya; Omelchenko, Hanna (Proceedings of National Aviation University (archive), 2017)
Purpose: clarify legal nature of relations emerging in connection with registration of patent law objects. In this article the authors research special features of legal regulation of inventive activity. In particular, they consider several issues of patenting the patent law objects and clarify legal nature of relations arose during registration of the rights to the patent law objects. Methods: formal legal and case-study methods together with inductive reasoning, and comparison were used to analyse the legislation in the area of jurisdiction inventive activity Results: during the research the authors focus their attention to the drawbacks of the effective legislation and form the main directions of the effective legislation improvement in accordance with international law in the context of the patent law objects protection. Special attention is devoted to analysis of the main threats of the patent law violations and ways to overcome them. Conclusions: the results confirming improving the efficiency of the system of intellectual property protection through institutional changes and changes in the legal regulation of inventive activity and results will have a positive impact on the reform of the system of intellectual property protection in Ukraine.